The New York Public Library's books of the century - Diefendorf, Elizabeth (Oxford University Press, 1996)
This volume takes readers on a thought-provoking tour of the 20th century, through the medium of the printed word. Here readers will find over 150 pivotal works organized into topical categories, reflecting themes that have informed the century. Each is introduced with a brief commentary illuminating the themes and issues the books in that section address, followed by an annotation for each title offering a brief description and a key to its significance.